Contemporary Human Resource Management : Text and Cases - Wilkinson, Adrian; Dundon, Tony; Yates, Edward (SAGE Publications, Ltd. (UK), 2025)
Written by experts in the field, the seventh edition of this well-established book provides a critical and academically rigorous exploration of the key functions, practices and issues in HRM today. The first part of Contemporary Human Resource Management covers fundamental HRM practices while the second half examines contemporary themes and issues such as technology and climate change. The book contains over 50 thought-provoking case studies, showing you how theory relates to real-world examples. This substantially revised seventh edition includes three completely new chapters and case studies on: Remote working  New technologies Social media Adrian Wilkinson is Professor of Employment Relations and Human Resource Management at Griffith University and Visiting Professor at the University of Sheffield.  Tony Dundon is Professor of HRM and Employment Relations at Kemmy Business School, University of Limerick and Visiting Professor at the Work and Equalities Institute, University of Manchester. Edward Yates is a Lecturer in Employment Relations and Human Resource Management at the University of Sheffield.